The Role of strategic innovation in achieving Organizational differentiation - Abbas Mazal Musharraf; Jinan Ali Abdoun (مجلة الغري للعلوم الاقتصادية والادارية)
Abstract The purpose of this study is to explore the relationship between the strategic innovation and the organizational differentiation. the main goal of this study is to find out if the strategic innovation has a direct effect on the Iraqi institutions ( Hospitals / in Babylon government ) based on the actual problems which directly effect on the organizations environment competent In the presentation services and identification. the Problem study with questions the important(questions): what is the role of the strategic innovation for achieving the organizational differentiation for the employees in the hospitals under research? the results of this study has shown that the essential technology, alignment the strategic, development a new services, disciplined ( accurate ) implementation, have a direct effect on the differentiation organization through coordinated role for the organizational developments , consequently this study intends to reduce the levels by the point of view of the that work on the organizational structure .